Integrated research of slaging intensityof the boilerunit heating surfaceswhen burning non-project fuels - E. A. Boiko; I. V. Zagorodnii (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Comprehensive research of the slagging intensity is the heating surfaces of the BKZ-420-140 boiler unit with solid slag removal at the Abakan CHP when burning non-project fuels. The relevance of the work is due to the technical necessity and economic feasibility of conversion boiler units to combustion of non-design coals. METHODS. The problem has been analyzed by methodology for conducting complex tests, measurements and processing of experimental data, as well as the results of experimental and computational studies of a boiler unit when operating on coals of various qualities. RESULTS. Qualitative and quantitative parameters for assessing the properties of off-design coals and their behavior in real operating conditions of radiation, semi-radiation and convective conditions, taking into account their modes and design functions, have been obtained. CONCLUSION: A computational analysis of the operating modes of boiler units when burning non-design fuels showed that a promising technology for involving non-design coals in the fuel and energy balance of a thermal power plant is providing a scientifically based mixture of design and nondesign fuels.Analysis of the slagging and polluting properties of non-design coals makes it possible to predict changes in the characteristics of the thermal efficiency of heating surfaces and to develop many practical recommendations for optimizing the parameters of the cleaning equipment installed on the boiler.Also, mixtures of fuels were determined for which the wall temperatures of the metal of the outlet stack of the superheater increase, which significantly reduces the strength characteristics of the surface.The assessment and prediction of the reliability of the heating surface is carried out by calculating the temperature of the metal wall in the most heat-stressed place.